Design and Development of Manually Operated Sapota Cleaner - Dabhi, M. N.; Davara, P. R. (Journal of Agricultural Engineering, 2018)
Cleaning of sapota is an important unit operation after harvesting. Harvested fruits are presently cleaned by manually rubbing with cloth. A manually operated sapota cleaner was designed and developed to reduce human drudgery. The cleaner was tested at 60, 65 and 70 rpm, and its batch capacity varied from 15 to 45 kg. The drum with jute cloth inner lining had cleaning efficiency of 99.95 % at 70 rpm rotational speed and 20 kg sapota batch load. At drum speed of 60 rpm and 20 or 30 kg of sapota load, no damage of fruit was observed. The cleaner gave best performance at 70 rpm drum speed, 20 kg feed /batch, giving 99.95 % cleaning efficiency and 2.04 % fruit damage. The cost of the cleaner was ` 7000, with cost saving of ` 0.30/kg sapota as compared to traditional cleaning method.